INSTITUTIONAL DETERMINANTS OF LOCAL FINANCIAL SUSTAINABILITY IN INDONESIA: A MULTIDIMENSIONAL INDEX APPROACH - Kustiani, Nur; Aryati, Titik; Herawaty, Vinola; Sustiyo, Joko (JRAK, 2026)
Indonesia faces an accountability contradiction where nearly all local governments achieve Unqualified (WTP) audit opinions despite persistent vertical fiscal imbalances and high dependency on central transfers. Addressing the normative shifts introduced by Law No. 1 of 2022 (UU HKPD), this study develops a Local Financial Sustainability (LFS) Index that bridges IPSASB RPG 1 with specific national pillars, namely spending quality and local independence. Analyzing 404 local governments over the 2022–2023 period using Panel Corrected Standard Error (PCSE), the findings reveal that spending efficiency and budget transparency are potent drivers of financial sustainability, signaling managerial effectiveness and reduced agency costs. Notably, contrary to sticky cost theory, administrative intensity exhibits a strong positive influence, acting as a proxy for the institutional capacity required for regulatory transitions. This research redefines fiscal health through productive expenditure and institutional maturity. Practically, the LFS Index provides a self-assessment tool and a performance-based framework for central policymakers in the UU HKPD era.